Improving The Competence of Batik Craftsmen in Liquid Waste Management Through Electrolysis Technology in Kampung Batik Gedong - Qudus, Nur; Harianingsih, Harianingsih; Sugiyarto, Bambang; Kristianto, Virgiawan Adi; Siswoyo, Mohammad Pujo; Pangestu, Indra Sakti; Ubay, Isnina Noor; Erliana, Savira Rinda (Journal of Community Empowerment, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) industry in Kampung Batik Gedong, Semarang, has made a significant contribution to the local economy through the production of Semarang's signature batik. However, this production activity produces liquid waste containing synthetic dyes and heavy metals, which have a negative impact on the environment. The lack of effective waste processing technology and the low knowledge and skills of MSMEs in waste management are major challenges that require immediate solutions. This community service program aims to increase the capacity of MSMEs in managing liquid waste sustainably through the application of electrolysis technology and integrated training. The activities are carried out in five stages: preparation, socialization, application, monitoring, and evaluation. The data collection method involves measuring the level of knowledge using pretests and posttests, as well as assessing skills through direct assessments by the service team. The target of the program's success is to increase the understanding of MSMEs implementer by 80% and skills by 75% after training. Electrolysis technology is applied to reduce the concentration of dyes and heavy metals in liquid waste, while training is provided to improve the understanding and technical skills of MSMEs implementer. The results of this program are expected to include reducing the level of liquid waste pollution, increasing the technical capacity of MSMEs implementer, and increasing awareness of the importance of environmental sustainability. Thus, this program supports environmental conservation, the sustainability of the batik industry, and the achievement of the Sustainable Development Goals (SDGs), especially SDGs 6 (Clean Water and Sanitation), SDGs 12 (Responsible Consumption and Production), SDGs 13 (Action on Climate Change), and SDGs 14 (Life Below Water).